Restoration of islamic religious Education in the order of social life - ajeng casika; ika ainun khasanah; masduki asbari (AGUSPATI RESEARCH INSTITUTA, 2022)
Abstract - This paper describes some of Muslim’s social problems in Indonesia, as like, social conflicts have been caused by different backgrounds, proverty, and life dis-orientation. It also concerns about the real condition that Islamic education which has not been given the contribution more toward the improvement of the condition. Finally, this paper suggests the importance of Islamic education to imply the human nature potential development to create well-conduct of human beings, exactly the human of individual both the spritual piety and social concern.